Building coherence and cohesion : task-oriented dialogue in English and Spanish - Taboada, María Teresa (Pragmatics & beyond, 2004)
This book examines the resources that speakers employ when building conversations. These resources contribute to overall coherence and cohesion, which speakers create and maintain interactively as they build on each other's contributions. The study is cross-linguistic, drawing on parallel corpora of task-oriented dialogues between dyads of native speakers of English and Spanish. The framework of the investigation is the analysis of speech genres and their staging; the analysis shows that each stage in the dialogues exhibits different thematic, rhetorical, and cohesive relations. The main contr.